The Oral Communication in Teaching Speaking Using Problem Based Learning on Vocational School Students - Kholis, Mukhammmad Nur (RETAIN, 2022)
This study aims to determine how teachers apply Oral Communication using PBL to help students develop their speaking skills. This study uses the qualitative method. Twelve vocational students were majoring in TKR (Light Vehicle Technical) participated in this study. This research implemented Problem Based Learning as it was integrated into the learning and teaching process. Two meetings were carried out in this study. The teacher explained the subjects' material normally at the first meeting. At the second meeting, the teacher applied Oral Communication using the PBL as a means of learning model, and it was found that the strategy used had been able to help students in speaking English. Therefore, Oral Communication using Problem Based Learning can help the students become more active in speaking English. Keywords: Speaking skill, oral communication, PBL, Vocational School.